Occurrence of respiratory viruses among outpatients with diarrhea in Beijing, China, 2019–2020 - Shen, Lingyu; Yan, Hanqiu; Li, Weihong; Tian, Yi; Lin, Changying; Liu, Baiwei; Wang, Yu; Jia, Lei; Zhang, Daitao; Yang, Peng; Wang, Quanyi; Gao, Zhiyong (Frontiers in Microbiology, 2023)
Objectives: To investigate respiratory virus infections in diarrhea cases and identify the risk of respiratory virus transmission through feces. Methods: Fecal specimens were collected from diarrhea cases in enteric disease clinics in Beijing, China, from 2019 to 2020. Cases that tested negative for norovirus, rotavirus, sapovirus, astrovirus, and enteric adenovirus were included in the study. Real-time RT-PCR was used to detect 16 groups of respiratory viruses, and the major viruses were genotyped. Viruses isolation and digestion of clinical specimens and nucleic acid by artificial gastric acid or artificial bile/pancreatic juice were used to evaluate the risk of respiratory virus transmission through feces. Results: A total of 558 specimens were collected and 47 (8.42%) specimens were detected positive, 40 (13.33%, 40/300) in 2019, and 7 (2.71%, 7/258) in 2020, including 20 (3.58%) for human rhinovirus (HRV), 13 (2.32%) for Bocavirus (BoV), 6 (1.08%) for parainfluenza virus I (PIV), 4 (0.72%) for coronavirus (CoV) OC43, 3 (0.54%) for respiratory syncytial virus (RSV) A, and 1 (0.18%) for both BoV and CoV OC43. SARS-CoV 2 and other viruses were not detected in this study. Eight genotypes were identified in the 13 HRV specimens. BoVs 1 and 2 were identified in nine BoV specimens. HRV infectious virions were successfully isolated from 2 clinical specimens and clinical specimens of HRV, RSV, PIV and CoV could not be detected after 4 hours of digestion and their nucleic acid could not be detected after 2 hours of digestion by artificial gastric acid or artificial bile/pancreatic juice. Conclusions: There may be a risk of respiratory virus transmission from diarrhea cases, and interventions against SARS-COV-2 epidemics are also effective for other respiratory viruses.